Incidence and Predictors of Imported Cases of COVID-19 in Burkina Faso - Kaboré, Mikaila; Sondo, Kongnimissom Apoline; Dahourou, Désiré Lucien; Cissoko, Yacouba; Konaté, Issa; Zaré, Abdoulaye; Bicaba, Brice; Ouedraogo, Boukary; Barro, Hermann; Diendéré, Eric Arnaud; Asamoah, Isabella; Damoue, Sandrine Nadège; et al. (Frontiers in Public Health, 2022)
Background: To limit the spread of COVID-19 due to imported cases, Burkina Faso has setup quarantine measures for arrival passengers. We aimed to determine the incidence and predictors of imported cases of COVID-19 in Burkina Faso. Methods: Prospective cohort study was performed using data from passengers arriving at the airport from April 9 to August 31, 2020. The data was extracted from the DHIS2 platform. Cox regression was used to identify predictors of imported cases of COVID-19. Results: Among 6,332 travelers who arrived in the study period, 173 imported cases (2.7%) were recorded. The incidence rate was 1.9 cases per 1,000 traveler-days (95%CI: 1.6-2.2 per 1,000). Passengers arriving in April (Adjusted hazard ratio [aHR]=3.56; 95%CI: 1.62-7.81) and May (aHR=1.92; 95% CI: 1.18-3.12) were more at risk of being tested positive compared to those arriving in August, as well as, passengers presenting with one symptom (aHR=3.71; 95% CI: 1.63-8.43) and at least two symptoms (aHR=10.82; 95% CI: 5.24-22,30) compared to asymptomatic travelers. Conclusions: Incidence of imported cases was relatively low in Burkina Faso between April and August, 2020. The period of travel and the presence of symptoms at arrival predicted the risk of being tested positive to SARS-CoV-2. This is essential in the context of high circulation of virus variants worldwide and low local capacity to perform genotyping tests to strengthen the surveillance and screening capacities at the points of entry into the country.